Youth perceptions of income inequality in six Southeast Asian countries - Halimatusa'diyah, Iim; Mohamad Shukri, Syaza Farhana (ISEAS Publishing, 2025)
While much research has explored how perceptions of income inequality influence political outcomes—such as political participation, behaviour, and support for democracy—less attention has been given to how a country’s economic and political conditions shape these perceptions. This article argues that economic outlook and political stability play a crucial role in shaping how youths perceive income inequality. A youth and civic engagement survey conducted by the ISEAS – Yusof Ishak Institute between August and October 2024 found that Indonesian, Filipino and Thai youths are the most pessimistic about the economic prospects and political conditions of their countries. This bleak outlook aligns closely with their negative perceptions of income inequality. In contrast, youths in Singapore and Vietnam exhibit higher levels of optimism, underpinned by the strong economic growth and political stability of their countries. These favourable conditions, in turn, contribute to more positive perceptions of fairness in wealth distribution in their respective countries. Malaysia, however, presents a more nuanced picture. Despite relatively high levels of income inequality, Malaysian youths remain optimistic about the economic future of the country, revealing a disconnect between economic optimism and perceptions of income inequality. Overall, this article urges policymakers to address objective measures as well as subjective perceptions of inequality by fostering economic environments and political systems that bolster youth optimism and confidence in equitable development. As these perceptions will shape future political landscapes significantly, ensuring a balanced narrative regarding economic growth and fair wealth distribution is essential for sociopolitical stability in Southeast Asia in the future.